Evaluation of cardiovascular demands of game play and practice in women's ice hockey - Spiering, B. A.; Wilson, M. H.; Judelson, D. A.; Rundell, K. W. (The Journal of Strength and Conditioning Research, 2003)
Preparation for the physical demands of competition often involves game simulation during practice. This paradigm is thought to promote physiological adaptations that enhance maximal performance. However, a mismatch between practice intensity and actual competition intensity may not provide adequate training to achieve optimal game-play fitness. The purpose of this study was to evaluate the effectiveness of practice in meeting the cardiovascular demands of a women's ice hockey game. Heart rate (HR) data from 11 U.S. National Women's Ice Hockey team members were collected (5-second intervals) during a game and a typical practice session. Data was normalized to individual HRmax determined during O2max testing. Working time was defined as a game shift or practice-working interval. Mean working HR was greater during the game than the practice, 90 ± 2% and 76 ± 3% of HRmax, respectively (p < 0.05). Mean percent session time (game or practice) >90% HRmax was also longer during the game than the practice, 10.5 ± 4.1% and 5.6 ± 3.5% (p < 0.05), respectively. Mean session HR, percent time >80% HRmax, and mean resting HR were not different between game and practice (68 ± 7% vs. 69 ± 5%, 23.2 ± 5.3% vs. 26.1 ± 9.2%, and 59 ± 8% vs. 56 ± 5%, respectively). Elite women hockey players experience significantly greater cardiovascular load during game play than during practice. This mismatch in cardiovascular demand may prevent players from achieving "game shape", thus affecting competition play.